Preparation, Microstructure, and Mechanical Properties of Spinel-Corundum-Sialon Composite Materials from Waste Fly Ash and Aluminum Dross. (30th January 2014) - Huang, Juntong; Fang, Minghao; Huang, Zhaohui; Liu, Yan'gai; Yang, Jingzhou; Huang, Saifang; Xu, Youguo; Chen, Kai; Yi, Shuai; Zhang, Shaowei
Abstract : The solid wastes fly ash and aluminum dross were used to prepare the low cost, high added-value product spinel-corundum-Sialon with an in situ aluminothermic reduction-nitridation reaction. The effects of varying raw material components and heating temperatures on the phase compositions, microstructure, bulk density, apparent porosity, and bending strength of products were investigated. The presence of hazardous or impure elements in the products was also evaluated. The sintered materials mainly consisted of micro-/nanosized plate corundum, octahedral spinel, and hexagonal columnar β -Sialon. The bulk density and bending strength of product samples initially increased and then decreased as Al content increased. Product samples with an Al content exceeding 10 mass% that were sintered at 1450°C exhibited the highest bending strength (288 MPa), the lowest apparent porosity (1.24%), and extremely low linear shrinkage (0.67%). The main impurity present was Fe5 Si3 with hazardous elements P, Cr, Mn, and Ni doping. This work could provide a new method to reduce environmental pollution and manufacture low cost high performance refractory materials using the abundant waste materials fly ash and aluminum dross.